Polycystic Ovarian Syndrome: Long-Term Health Consequences - Zore, Temeka; Joshi, Nikhil V.; Lizneva, Daria; Azziz, Ricardo (Seminars in Reproductive Medicine, 2017)
Polycystic ovarian syndrome (PCOS) is the most common endocrinopathy in women and can be associated with significant adverse sequelae that can affect overall long-term health and well-being. This review provides a succinct but comprehensive overview of our current understanding concerning the known morbidities of PCOS, beginning with a review of the importance of the different phenotypes of PCOS in determining long-term morbidity, the confounding impact of obesity on health outcomes in PCOS, and the immediate short-term consequences of the disorder (including dermatologic, reproductive, and mood disturbances). The longer-term morbidities of PCOS are then reviewed including metabolic consequences (impaired glucose tolerance and type 2 diabetes mellitus, metabolic syndrome, and nonalcoholic fatty liver disease), dyslipidemia and vascular dysfunction (including hypertension and increased incidences of cerebrovascular accidents and thromboembolisms on oral contraceptives), neoplastic (primarily endometrial adenocarcinoma), and mental health disorders (including greater incidences of depressive and anxiety disturbances and psychosexual dysfunction). In conclusion, strategies for the prevention and amelioration of long-term morbidities in PCOS are presented.
Keywords: polycystic ovarian syndrome; health consequences; metabolic dysfunction; cardiovascular disease; type 2 diabetes mellitus; endometrial adenocarcinoma; breast cancer; hypertension; depression; anxiety